2015
DOI: 10.1371/journal.pone.0122086
|View full text |Cite
|
Sign up to set email alerts
|

Female Employment Reduces Fertility in Rural Senegal

Abstract: Economic growth and modernization of society are generally associated with fertility rate decreases but which forces trigger this is unclear. In this paper we assess how fertility changes with increased labor market participation of women in rural Senegal. Evidence from high-income countries suggests that higher female employment rates lead to reduced fertility rates but evidence from developing countries at an early stage of demographic transition is largely absent. We concentrate on a rural area in northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…In Botswana, a study found that nonworking mothers had more number of children ever born than their working counterparts [38]. Relatedly, in women's participation in labor force was found to reduce fertility rates [39]. In Poland, work was found to have a direct effect on the number of births with women who work having more children than their counterparts who did not work [3].…”
Section: Discussionmentioning
confidence: 99%
“…In Botswana, a study found that nonworking mothers had more number of children ever born than their working counterparts [38]. Relatedly, in women's participation in labor force was found to reduce fertility rates [39]. In Poland, work was found to have a direct effect on the number of births with women who work having more children than their counterparts who did not work [3].…”
Section: Discussionmentioning
confidence: 99%
“…In Chinese context, the type of women's employment is a factor that affected women's fertility intentions: workers, civil/professionals, and business managers had the lowest fertility intentions, whereas farmers had the highest fertility intentions (Zheng and al., 2016). Many studies in developed countries found a negative relationship between fertility and women's labor force participation (Van and Maertens, 2015;Michaud & Tatsiramos, 2011). However, evidence of negative effect of the number of children on women's labor force participation from developing countries at an early stage of demographic transition is less consistent (Agüero & Marks, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, employed women have a higher opportunity cost of raising children, and substitute productive labor for reproductive labor. This substitution effect results in decreased fertility (Van, 2015). Another mechanism of women's occupation on fertility is women's empowerment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Beguy (2009) suggests that women's participation in the labour market is not associated with a decline in fertility in the city of Dakar. In turn, in rural, northern Senegal an increase in female off-farm labour due to a boom in horticulture exports led to a lower fertility rate (Van den Broeck & Maertens, 2015).…”
mentioning
confidence: 99%